Eyelid Warming Devices: Safety, Efficacy, and Place in Therapy - Bzovey B; Ngo W (Clinical Optometry, 2022)
Brandon Bzovey,1 William Ngo2,3 1Centre for Ocular Research & Education, School of Optometry & Vision Science University of Waterloo, Waterloo, Ontario, Canada; 2School of Optometry & Vision Science, University of Waterloo, Waterloo, Ontario, Canada; 3Centre for Eye and Vision Research (CEVR), Hong Kong, People’s Republic of ChinaCorrespondence: William Ngo, School of Optometry & Vision Science, University of Waterloo, Waterloo, ON, N2L 3G1, Canada, Tel +519-888-4567 x 40857, Email wngo@uwaterloo.caAbstract: Meibomian gland dysfunction (MGD) is characterized by the obstruction and/or inflammation of the meibomian glands that result in decreased and altered meibum secretion. This results in deficiencies in the tear film lipid layer which contributes to increased evaporation and destabilization of the tear film. One of the mainstay therapies for MGD is medical devices that apply heat and/or pressure to the eyelids and promote the liquification and outflow of meibum into the tear film. Over the past two decades, there have been a surge of interest in diagnosing and managing MGD. As a result, numerous medical devices have been developed and each have their own unique approach to treating MGD. This narrative review was conducted to summarize the current state of knowledge on eyelid warming devices, specifically warm eye coverings, devices that direct heat and/or pressure to the eyelids, moisture chamber goggles, and light-based therapy. This review summarized 58 human clinical studies and found that most eyelid warming devices were efficacious in improving signs and symptoms in a wide range of MGD severities and were generally safe to use.Keywords: dry eye, meibomian gland dysfunction, warm compresses, thermal pulsation, moisture chamber goggles, intense pulsed light